Implementation of Social Determinants of Health Screening in a Student-Run Physical Therapy Pro Bono Clinic - Stickler, Laurie; Chesser, Brianna; Sander, Todd; Bonhaus, Katelyn (Journal of Student-Run Clinics, 2025)
Addressing non-medical factors impacting health is essential for health equity. While addressing social determinants of health (SDOH) has become a standard in primary care, it is vital within rehabilitation services as well. This report describes the implementation of screening for SDOH at a university pro bono physical therapy clinic in an urban community. Insights into best practices for implementation were outlined and a nine-question SDOH screening questionnaire was developed. Baseline data of 80 clients identified access to healthy food and payment of basic expenses as the most common SDOH requiring follow-up. Several considerations for implementation were identified including the complex nature of factors impacting care and the need for thoughtful follow-up questions to provide appropriate resources and care.